4
$\begingroup$

Can someone help me finding the expected value of the solution to Merton's jump diffusion model:

\begin{align} S_t &= S_0 \exp \left( \left(r - \frac{\sigma^2}{2} - \lambda k \right) t + \sigma W_t \right) \prod_{j=1}^{N_t} (1+\epsilon_i) \end{align}

where $W_t$ is a BM and $N_t$ is a Poisson process with intensity $\lambda$ and $k$ is the expectation of $\epsilon_i$. The Brownian Motion and Poisson Process are independent.

I know that

\begin{align} E \left[ \exp \left( \left(r - \frac{\sigma^2}{2} \right) t + \sigma W_t \right) \right] = \exp(rt) \end{align}

but what is

\begin{align} E \left[ \prod_{j=1}^{N_t} (1+\epsilon_i) \right] = ? \end{align}

$\endgroup$
  • $\begingroup$ The product of $N_t$ factors. $\endgroup$ – Gordon Oct 8 '17 at 19:02
  • $\begingroup$ Can you elaborate a little bit? $\endgroup$ – Andrew Oct 8 '17 at 19:48
  • $\begingroup$ For a given sample $\omega$, $N_t(\omega)$ is an integer. $\endgroup$ – Gordon Oct 8 '17 at 20:22
  • $\begingroup$ Hint: you can leverage the law of iterated expectations (or total expectations) to deal with the random variable $N_t$. $\endgroup$ – Daneel Olivaw Oct 8 '17 at 21:14
  • $\begingroup$ So if I condition on the number of jumps to be n then there will be n terms in the product and since each jump is independent the expectation will become $(1+k)^n$ ? I know that I am supposed to get $\exp(\lambda k t)$ but how can I get that from $(1+k)^n$ ? $\endgroup$ – Andrew Oct 8 '17 at 21:42
7
$\begingroup$

Given for all $i$ the mean of $\epsilon_i$ is $k$ and that the $\{\epsilon_i\}_i$ are i.i.d., we have$^{\text{(1)}}$:

$$\begin{align} E\left[\prod_{i=1}^{N_t}(1+\epsilon_i)\right] &=E\left[E\left[\prod_{i=1}^{N_t}(1+\epsilon_i)|N_t\right]\right] \\[6pt] &=E\left[\prod_{i=1}^{N_t}E\left[(1+\epsilon_i)|N_t\right]\right] \\[6pt] &=E\left[\prod_{i=1}^{N_t}(1+k)\right] \\[13pt] &= E\left[(1+k)^{N_t}\right] \end{align}$$

By definition of the expectation and the distributional properties of $N_t$:

$$\begin{align} E\left[(1+k)^{N_t}\right]&=\sum_{n=0}^{\infty}(1+k)^{n}\frac{(\lambda t)^n}{n!}e^{-\lambda t} \\[6pt] &= e^{k\lambda t} \end{align}$$

$\text{(1)}$ Note a subtlety here that got me momentarily confused: the product of $n$ i.d.d. random variables $\epsilon_1,\cdots,\epsilon_n$ with same distribution as $\epsilon$ is not the same as the $\text{n}^{\text{th}}$ power of variable $\epsilon$. Hence, you cannot directly collapse the product $\prod_{1\leq i \leq n}(1+\epsilon_i)$ to the power $(1+\epsilon)^n$, you first need to "inject" the expectation into the product.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.